Concise synthesis of (-)-deoxoprosopinine - Pandey, Satyendra Kumar; Kumar, Pradeep (Synlett, 2007)
A simple and highly efficient approach to (-)-deoxoprosopinine from racemic epoxide as a starting material is described employing a Jacobsen's hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD) as key steps.
Keywords: hydroboration-oxidation; Jacobsen's HKR; Piperidine alkaloids; sharpless AD; Total synthesis